Controller design for PMSG wind turbine - Peng, Di. (2011)
In recent years, world energy crisis is getting serious. Much new energy is found to take the position of fossil fuels. Wind power has become more and more popular all over the world because it is renewable, clean and plentiful. At the same time it products no greenhouse gas emissions during operation.